2021
DOI: 10.1101/2021.03.21.436320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gastruloids asin vitromodels of embryonic blood development with spatial and temporal resolution

Abstract: Gastruloids are three-dimensional embryonic organoids that reproduce key features of early mammalian development in vitro with unique scalability, accessibility, and spatiotemporal similarity to real embryos. Recently, we adapted gastruloid culture conditions to promote cardiovascular development. In this work, we extended these conditions to capture features of embryonic blood development through a combination of immunophenotyping, detailed transcriptomics analysis, and identification of blood stem/progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Therefore, gastruloids could perhaps also be used as a source of organoids or tissues for transplantation purposes in clinical settings. In line with this idea, recent work suggested that it might be possible to derive brain organoids [46], to derive endodermal cell types that are difficult to obtain with 2D cultures [22], or to derive transplantable blood progenitors [62] from mouse gastruloids.…”
Section: Large-scale Screeningsmentioning
confidence: 99%
“…Therefore, gastruloids could perhaps also be used as a source of organoids or tissues for transplantation purposes in clinical settings. In line with this idea, recent work suggested that it might be possible to derive brain organoids [46], to derive endodermal cell types that are difficult to obtain with 2D cultures [22], or to derive transplantable blood progenitors [62] from mouse gastruloids.…”
Section: Large-scale Screeningsmentioning
confidence: 99%
“…Improvements in culturing conditions, such as embedding in Matrigel or fusion of a pulsed and non-pulsed EB, enhanced tissue organization and led to the formation of somite-like and neural structures (190)(191)(192). Single cell transcriptomics of gastruloids of different "developmental stages" and culturing methods showed different mesodermal derived populations with expression of endothelial and early blood markers like Etv2, Kdr, Cdh5, Kit, Gata2, Runx1, Cd34 and Itga2b (190,191,193). This suggests that gastruloids produce a hemangioblast-like cell type that might differentiate into endothelial, HE and/or even early HSPCs.…”
Section: Recapitulating the Endogenous Hsc Niche In 3d-culture Systems To Produce Bona Fide Hscs And Other Blood Forming Cellsmentioning
confidence: 99%
“…This suggests that gastruloids produce a hemangioblast-like cell type that might differentiate into endothelial, HE and/or even early HSPCs. Conformingly, detailed analysis of endothelial and blood markers in gastruloids revealed the formation of a vascular plexus, the production of blood progenitors and erythroid-like populations ( 193 ). The presence of blood vessel like structures and expression of markers like Kit, Itga2b and Runx1 is suggestive for the presence of HE cells and/or pre-HSCs, although additional functional assays are needed to confirm whether gastruloids can produce such cell types.…”
Section: Recapitulating the Endogenous Hsc Niche In 3d-culture Systems To Produce Bona Fide Hscs And Other Blood Formimentioning
confidence: 99%